Триггерная роль COVID-19 в развитии сахарного диабета 1-го типа и кетоацидоза у ребенка: случай из практики - V. V. Sokolovskaya; A. A. Litvinova; N. N. Smolyankin; A. V. Krikova; R. S. Kozlov (Детские инфекции (Москва))
It has been proven that the SARS-CoV-2 virus is able to initiate the development of a number of metabolic disorders, leading to diabetes mellitus (DM). Given the high frequency of cases of newly diagnosed type 1 diabetes in children, as well as possible adverse prospective consequences, the study of such clinical cases seems to us to be an extremely relevant practice for doctors of all specialties. The aim of the study was to to demonstrate of a clinical case of newly diagnosed type 1 diabetes in a child with COVID-19.The article presents a general understanding of the pathogenetically bidirectional relationship between a new coronavirus infection and diabetes mellitus, presents a clinical case of type 1 diabetes diagnosed for the first time in a child 3 years 8 months with COVID-19, and describes the further stage of treatment in the specialized endocrinology department.Conclusion. The clinical case presented by us, as well as data obtained as a result of research by domestic and foreign colleagues, confirm the existence of a pathogenetically determined relationship between COVID-19 and type 1 diabetes mellitus in children. To better understand the mechanisms underlying the devel- opment of metabolic suffering, it is necessary to create a single Global registry of patients with diabetes mellitus, first identified in connection with COVID-19.